Investigation of Measles Outbreak in a School, Blora District, Central Java, Indonesia 2016 - ahmad musyafa (Berita Kedokteran Masyarakat (BKM), 2017)
Background: On December 6, 2016 Blora District Health Office (DHO) received a reports of four suspected measles cases from Jiken Public Health Centers (PHC). All cases were from a Public High School.  Field investigation was conducted to characterize the outbreak. Methods: We conducted active case finding to find additional cases. We defined a case as students from affected high school with skin rash and influenza like syndrome and/or conjunctivitis, and/or blood test positive for IgM for measles during August 29 to December 28, 2016. Primary data were collected by interviewing patients and their parents or care giver. Secondary data were collected from Blora DHO, PHC and schools.Results: Of 270 students, 44 were matched to our case definition. We found 14 cases were from a high school. The first case was a student who had sibling with measles in his house and student of a Kindergarten. Additional 27 cases were identified during our investigation in the Kindergarten. We found that the first case in this kindergarten have had a contact with her family who had measles after returned form other province. Of 44 cases, 14 cases were from high school, 27 from kindergarten, and 3 cases from community. The highest Attack Rate (AR,56.8%) was children aged 5 – 10 years, children who attend kindergarten (39.7%).Immunization coverage data was not available at DHO or PHC, and most of the care giver were no remember the measles immunization status of their children.  Conclusion: The measles outbreak has a Public High School and a Kindergarten in from Agust-Desember 2016. The late detection of measles cases has contributed to this outbreak. Improvement of immunization and surveillance systems for prevention of future outbreak. Provision of Vitamin A and ORI was conducted to contain the outbreak